Nepheline syenite and phonolite as alternative potassium sources for maize - Nogueira, Thiago Assis Rodrigues [UNESP]; Miranda, Bruno Gasparoti [UNESP]; Jalal, Arshad [UNESP]; Lessa, Luís Gustavo Frediani [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Marcante, Nericlenes Chaves; Abreu-Junior, Cassio Hamilton; Jani, Arun Dilipkumar; Capra, Gian Franco; Moreira, Adônis; Martins, Éder de Souza (MDPI, 2021)
Some silicate rocks are a rich source of potassium (K), with the possibility for use in agriculture. The present study aimed to evaluate the agronomic efficiency index (AEI) of nepheline syenite (NS) and phonolite (PN) rocks in comparison with potassium chloride (KCl) as a K source in maize production. An experiment was conducted in a greenhouse in Ilha Solteira, São Paulo, Brazil. A maize hybrid was grown in 8 L pots filled with 6 kg of soil with a low K concentration and contrasting physical attributes (medium and sandy texture). A completely randomized design in a 3 × 6 factorial scheme was used, consisting of three K sources (NS, PN, and KCl) and six rates (0, 50, 100, 150, 200, and 400 mg kg−1) with four replications. All plants were harvested 45 days after emergence to evaluate biomass production, macronutrient (N, P, K, Ca, Mg, and S) concentration and uptake, stem diameter, and leaf chlorophyll index. After crop harvest, soil was collected for further chemical evaluation, which included organic matter (OM), pH, cation exchange capacity (CEC), H+Al, Al, sum of bases (SB), base saturation (BS), P, K, Ca, Mg, and S. In addition, AEI of NS and PN were also verified in relation to KCl. The application of NS and PN had a similar effect on soil chemical attributes (MO, pH, SB, CEC, and BS) as well as on the concentrations of K, Ca, Mg, and S, in both soils. The increase in NS and PN rates provided linear growth of shoot dry matter. Leaf macronutrient concentrations were similar for NS and PN compared to KCl. All three K sources (NS, PN, and KCl) increased K accumulation in maize plants. Maize treated with KCl had the largest AEI, followed by PN and NS. However, the results indicated similar AEI with both rocks as a K source for maize, especially with application of the highest K rates. This research demonstrated the efficiency of NS and PN as alternative K sources for maize.
Keywords: Agronomic efficiency index; Igneous rock; Rock powder; Zea mays L